Corruption in Indonesia: A Culturally Embedded Deviant Behavior and Efforts for Its Eradication - Sunarso; Rohid Arya Wiratama (Proceedings of International Conference of Graduate School on Sustainability, 2026)
Corruption in Indonesia has become a systemic and structural phenomenon deeply embedded within the fabric of society, leading many to describe it as a culture of corruption. This study explores the dynamics of corrupt behavior through a systematic literature review, focusing on empirical research and contemporary theoretical frameworks. The findings reveal that corruption in Indonesia has historical roots dating back to the pre-independence era and persists today. Rather than being an inherent cultural trait, corruption represents a deviant behavior that has become normalized through habitual practice and social tolerance. The relationship between culture and corruption is evident in the way corruption manifests as a social phenomenon grounded in cultural structures and paternalistic-clientelist mindsets, where loyalty to authority figures often takes precedence over integrity. The persistence of corruption is reinforced by cultural norms that tend to be permissive toward unethical conduct. This study underscores the need for a comprehensive anti-corruption movement involving educational institutions, local communities, traditional authorities, the media, public figures, and exemplary leadership among government officials and politicians. Such collaboration is essential for cultivating an anti-corruption ecosystem in which the interaction of values, norms, role modeling, and social control naturally fosters social resistance to corruption. Transformation of values cannot be achieved solely through law enforcement but must also involve socio-cultural and institutional reform. Every individual must be instilled with the values of honesty, responsibility, integrity, and concern for the public interest through education, exemplary leadership, and social habituation. State institutions should be built upon the principles of good governance that uphold integrity and prioritize public trust. Equally important, society, as a socio-cultural system, must transform its perspectives and behaviors that are permissive of corruption by firmly rejecting all forms of corruption. Through evidence-based analysis, this study contributes to the development of comprehensive and sustainable anti-corruption policies and strategies.